معوقات تطبيق أسلوب الموازنة التعاقدية في المجالس البلدية دراسة ميدانية (Economic studies journal, 2024)
The budgeting method has developed in many countries of the world and has shifted from the traditional method to modern methods, including the contractual budgeting method, and Libya is still preparing its budgets according to the traditional method, and therefore it is difficult to apply it now in Libya due to the lack of the necessary requirements for its application in the Libyan environment, according to what I found. Some studies in Libya indicate that there are obstacles that prevent its implementation, which places these obstacles the subject of study to identify them and try to address them.The descriptive analytical approach was relied upon in analyzing the data through the statistical program (SPSS). Statistical tools were used such as the arithmetic mean, standard deviation, one-sample T-test, and the one-way analysis of variance test. The study concluded that there are many obstacles that prevent the application of the method. Contractual budgetFor example, but not limited to, the political and economic conditions prevailing in Libya, the lack of clarity of the true meaning of this method and the mechanisms for its application, the high costs of its application, and the lack of qualified and trained human cadres capable of applying it. The study recommended the necessity of creating the appropriate climate through developing administrative and financial laws and legislation and providing material and human capabilities and accounting systems. And advanced management
Keywords: Contractual Budget; Projet contracts BOT; Municipal councils